An analysis of the role of labour relations practitioners as change agents : a case study on the Department of Defence - Qwele, Gcobani (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2009.